An Analyzing of Non-Observance Maxim Types in “24 Jam Bersama Gaspar” Movie - Nessa Yuanita (CV. Akademi Merdeka, 2025)
This present study aims to analyze the non-observance maxims of one selected film. In addition to that, this current study is conducted to investigate the conversational implicature can generate in the film. The analysis of non-observance of Grice's maxims in movies is rooted in the field of pragmatics, particularly focusing on how communication unfolds beyond literal meanings. The movie 24 Hours with Gaspar is used as the object of research, providing relevant data and highlighting the role of language in human communication. This study is descriptive qualitative to collect, analyze and report the data. Earlier, the researcher watches to find dialogues related to non-observances maxims. Afterwards, the researcher remarking and identify the dialogue and calculating the amount of the data. Lastly, the researcher analyzes and categorized the related dialouges based on Grice’s theory, determining the most dominant type, and write a conclusion. The researcher found 5 dialog involving non-observance maxim, which are: opting out quantity, violating relation, violating quantity, floating quantity and foating relation. Those data were differentiated in 2 conversational implicature namely generalized and particularized.